Sosialisasi dan Implementasi Pembuatan Kartu Identitas Anak (KIA) pada Warga Kelurahan Pasuluhan, Walantaka - Kota Serang - Fiana, Marista; Komariah, Ade; Ningsih, Rastia; Fikri, Riki Ukhtul; Nuryanto, Uli Wildan; Subroto, Desty Endrawati; Muti'ah, Eva; Romlah, Siti; Ichwanudin, Muhamad (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
This research aims to assess the effectiveness of the socialization and implementation of the Child Identity Card (KIA) program in Pasuluhan Village, Walantaka, Serang City. The KIA program, which is based on Minister of Home Affairs Regulation Number 2 of 2016, aims to provide official identity to children aged 0-17 years, as part of population administration efforts and protection of children's rights guaranteed by the constitution. Qualitative data was collected through interviews and observations at the Serang City Population and Civil Registration Service. This research found that KIA is important as additional identity for Birth Certificates and Family Cards. The research results revealed that although MCH is considered important as additional identity besides Birth Certificates and Family Cards, there is criticism regarding its effectiveness because children are already recorded on these documents. Better socialization is considered important to increase public understanding of the benefits and procedures for making KIA. Based on these findings, it is recommended that the KIA program continue to be improved and perfected so that it is more efficient and provides greater benefits for the community.